Air pollution and fecundability: Results from a Danish preconception cohort study. Issue 1 (10th December 2021) - Wesselink, Amelia K.; Wang, Tanran R.; Ketzel, Matthias; Mikkelsen, Ellen M.; Brandt, Jørgen; Khan, Jibran; Hertel, Ole; Laursen, Anne Sofie D.; Johannesen, Benjamin R.; Willis, Mary D.; Levy, Jonathan I.; Rothman, Kenneth J.; et al.
Abstract: Background: Animal and epidemiologic studies indicate that air pollution may adversely affect fertility. Epidemiologic studies have been restricted largely to couples undergoing fertility treatment or have retrospectively ascertained time‐to‐pregnancy among pregnant women. Objectives: We examined the association between residential ambient air pollution and fecundability, the per‐cycle probability of conception, in a large preconception cohort of Danish pregnancy planners. Methods: During 2007–2018, we used the Internet to recruit and follow women who were trying to conceive without the use of fertility treatment. Participants completed an online baseline questionnaire eliciting socio‐demographic characteristics, lifestyle factors, and medical and reproductive histories and follow‐up questionnaires every 8 weeks to ascertain pregnancy status. We determined concentrations of ambient nitrogen oxides (NOx ), nitrogen dioxide (NO2 ), carbon monoxide (CO), ozone (O3 ), particulate matter <2.5 µm (PM2.5 ) and <10 µm (PM10 ), and sulphur dioxide (SO2 ) at each participant's residential address. We calculated average exposure during the year before baseline, during each menstrual cycle over follow‐up and during the entire pregnancy attempt time. We used proportional probabilities regression models to estimate fecundability ratios (FRs) and 95% confidence intervals (CIs), adjusting for potential confounders and co‐pollutants. The analysis was restricted to the 10, 183 participants who were trying to conceive for <12 cycles at study entry whose addresses could be geocoded. Results: During 12 months of follow‐up, 73% of participants conceived. Higher concentrations of PM2.5 and PM10 were associated with small reductions in fecundability. For example, the FRs for a one interquartile range (IQR) increase in PM2.5 (IQR = 3.2 µg/m 3 ) and PM10 (IQR = 5.3 µg/m 3 ) during each menstrual cycle were 0.93 (95% CI: 0.87, 0.99) and 0.91 (95% CI: 0.84, 0.99), respectively. Other air pollutants were not appreciably associated with fecundability. Conclusions: In this preconception cohort study of Danish women, residential exposures to PM2.5 and PM10 were associated with reduced fecundability.